The role of outgroup homogeneity and the neurodynamics of the frontal cortex during beauty comparisons - George Zacharopoulos (Social Neuroscience, 2023)
The distance effect states that the closer two compared magnitudes (e.g., two numbers, physical attractiveness in two faces), the more difficult the comparison, and the greater the activity of the frontoparietal control network. However, it is unclear whether this network is also recruited to the same extent when we perform ingroup and outgroup beauty comparisons and whether the activation of these networks is tracked by interindividual variation in the perceptions we hold about an outgroup. We recorded brain activity with fMRI, where participants compared the beauty of two women ostensibly either from their ingroup or from an outgroup. Low-distance conditions produced longer response times than the high-distance conditions, and this was found in both the ingroup and outgroup conditions. However, our neuroimaging analyses revealed that the left IFG/anterior insula showed the classic distance effect only during ingroup processing but not during outgroup processing. Notably, interaction-specific activity within the left IFG/anterior insula was related to perceptions of outgroup homogeneity assessed via a questionnaire. This set of findings reveals the dynamic role of the prefrontal cortex and its interplay with perceptions of outgroup homogeneity in shaping ingroup and outgroup decision-making.